ANALISIS PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT SAMARTHA SOLUSI INDONESIA - Amelia, Dina Riska; Irawan, Roy (Cahaya Ilmu Bangsa, 2024)
The objective of this research is to examine the effects of motivation and work discipline on employee performance. Data collection was carried out using a questionnaire, and explanatory methods were utilized as the research design. This study involves two independent variables, namely motivation and work discipline, and one dependent variable, which is employee performance. The sample consisted of 30 respondents employed by the company. Multiple Regression Analysis was applied to analyze the data. The detailed findings indicate that work motivation has a positive and significant impact on employee performance, as evidenced by a probability value of Sig 0.000 < 0.05, thus supporting the first hypothesis. Similarly, the results for the second hypothesis reveal that work discipline also has a positive and significant effect on employee performance, with a probability value of Sig 0.000 < 0.05, thus confirming the second hypothesis. The third hypothesis is validated by the findings that motivation and work discipline together have a positive and significant impact on employee performance, with a probability value of Sig 0.000 < 0.05. In conclusion, this research demonstrates that both motivation and work discipline significantly influence employee performance, both individually and jointly. Keyword : Motivation, Work Discipline, Performance